2012
DOI: 10.4103/2278-9626.101355
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of dental caries among five-year-old school children in Shimla city, Himachal Pradesh

Abstract: Objective:The purpose of the study was to assess the prevalence of dental caries among five year old school children in Shimla city-Himachal Pradesh. Materials and Methods: The sample consisted of 800 school going children 421 (52.62%) boys and 379 (47.38%) girls from government primary schools which were selected randomly from four different zones of Shimla city. Type -III examination was conducted. The data obtained was analyzed by SPSS version 15 ( Inc., Chicago) using proportion test for comparison. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…They included 5-year-old schoolchildren of Shimla city in their study. [ 9 ] In another survey at Kangra district of Himachal Pradesh, in which oral health status of children in the age group of 5–12 years was assessed. In the age group of 5–8 years, they reported 56.8% of caries prevalence which is slight more than our study.…”
Section: Discussionmentioning
confidence: 99%
“…They included 5-year-old schoolchildren of Shimla city in their study. [ 9 ] In another survey at Kangra district of Himachal Pradesh, in which oral health status of children in the age group of 5–12 years was assessed. In the age group of 5–8 years, they reported 56.8% of caries prevalence which is slight more than our study.…”
Section: Discussionmentioning
confidence: 99%
“…These early erupted teeth exposed to risk factors responsible for initiation and progression of dental caries. Hence it is logical to assume that female subjects teeth would decay more than the teeth of the male subjects of the [11] same age. Bhardwaj et al revealed contrasting results showing male students with high prevalence of dental caries than among females.…”
Section: Discussionmentioning
confidence: 99%
“…During this period, oral hygiene is poor not only because of the carefree age and the emotional stresses of the child, but mainly because of frequent intake of refined sugars, soft and sticky foods, shedding of deciduous teeth and the It is crucial to control the disease process by assessing and rendering the treatment required along with spreading awareness regarding prevention. Many studies have been conducted in India and globally which reveal the prevalence of [7], [8], [9], [10], [11] dental caries among different populations.…”
Section: Introductionmentioning
confidence: 99%
“…Two independent reviewers on screening the remaining data, finally included 70 articles in this meta-analysis after excluding 25 articles due to studies lacking the prevalence rate of dental caries, no specification of DMFT index and age not matching with the inclusion criteria. [ 8 9 , 13 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 81 82 83 84 85 86 87 ]…”
Section: R Esultsmentioning
confidence: 99%